Characterization of fatty acid desaturases reveals stress-induced synthesis of C18 unsaturated fatty acids enriched in triacylglycerol in the oleaginous alga Chromochloris zofingiensis - Tao Wu; Lihua Yu; Yu Zhang; Jin Liu (Biotechnology for Biofuels, 2021)
Abstract Background The green microalga Chromochloris zofingiensis is capable of producing high levels of triacylglycerol rich in C18 unsaturated fatty acids (UFAs). FA desaturation degree is regulated by FA desaturases (FADs). Nevertheless, it remains largely unknown regarding what FADs are involved in FA desaturations and how these FADs collaborate to contribute to the high abundance of C18 UFAs in triacylglycerol in C. zofingiensis. Results To address these issues, we firstly determined the transcription start sites of 11 putative membrane-bound FAD-coding genes (CzFADs) and updated their gene models. Functional validation of these CzFADs in yeast and cyanobacterial cells revealed that seven are bona fide FAD enzymes with distinct substrates. Combining the validated functions and predicted subcellular compartments of CzFADs and the FA profiles of C. zofingiensis, the FA desaturation pathways in this alga were reconstructed. Furthermore, a multifaceted lipidomic analysis by systematically integrating thin-layer chromatography, gas chromatography–mass spectrometry and liquid chromatography–mass spectrometry techniques was conducted, unraveling profiles of polar membrane lipids in C. zofingiensis and major desaturation steps occurring in these lipids. By correlating transcriptional patterns of CzFAD genes and changes of lipids upon abiotic stress conditions, our results highlighted collaboration of CzFADs for C18 UFA synthesis and supported that both de novo FA synthesis and membrane lipid remodeling contributed C18 UFAs to triacylglycerol for storage. Conclusions Taken together, our study for the first time elucidated the pathways of C18 FA desaturations and comprehensive profiles of polar membrane lipids in C. zofingiensis and shed light on collaboration of CzFADs for the synthesis and enrichment of C18 UFAs in triacylglycerol.